Analisa Sistem Informasi Perpustakaan Berbasis Website Menggunakan Metode OOAD Pada SDS IT Asy-Syakur Cikarang - Eko Budiarto; Regina Febrianti (DPPM Universitas Pelita Bangsa, 2023)
The school library is an important facility that supports the learning process and enhances students’ knowledge. The SDS IT Asy-Syakur library still uses a manual system for borrowing and returning books, which often causes recording errors and difficulties in report preparation. Additionally, there is no information system capable of processing transactions quickly, generating reports efficiently, and storing data securely. This study aims to develop a web-based library information system using PHP with the Laravel framework and a MySQL database, developed using the OOAD method. The results show that the implemented system facilitates library monitoring, improves the speed and accuracy of borrowing and returning processes, enables faster report generation, and ensures secure data storage through database integration. Therefore, the implementation of this web-based library information system improves the efficiency of library management at SDS IT Asy-Syakur.